1987
DOI: 10.1037/h0079125
|View full text |Cite
|
Sign up to set email alerts
|

Imagery as an aid in working through unconscious conflicts: A preliminary report.

Abstract: A technique innovation designed to aid the working-through process in psychoanalytic treatment is considered. It consists of an analysand, either during or after treatment, imploding psychodynamic themes that have come to be understood as crucially involved in his or her psychology and psychopathology. ("Imploding psychodynamic themes" refers to the person conjuring up affectladen images in which warded-off libidinal and aggressive impulses are expressed and then met with punishment-e.g., abandonment or castra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…But that aside, Johnson's main concern is that readers will regard bioenergetic techniques as mere human potential tricks. Despite a growing interest in integrating, perhaps reintegrating, abreactive methods into psychoanalytic psychotherapy (e.g., Appelbaum, 1982; Silverman, 1987), the use of such techniques in psychoanalytically oriented treatment remains controversial.…”
Section: The Psychotherapy Of Narcissismmentioning
confidence: 99%
“…But that aside, Johnson's main concern is that readers will regard bioenergetic techniques as mere human potential tricks. Despite a growing interest in integrating, perhaps reintegrating, abreactive methods into psychoanalytic psychotherapy (e.g., Appelbaum, 1982; Silverman, 1987), the use of such techniques in psychoanalytically oriented treatment remains controversial.…”
Section: The Psychotherapy Of Narcissismmentioning
confidence: 99%
“…At the highest level of directiveness are structured imagery exercises th at are intended to therapeutically correct, rather than simply uncover, intrapsychic dynamics (Ahsen, 1968;Desoille, 1965;Leuner, 1969Leuner, , 1977Shorr, 1972Shorr, , 1974Singer, 1971aSinger, , 1971bSinger, , 1974. Most recently, from a decisively psychoanalytic perspective, Silverman (1987) proposed imagery as an aid in working through unconscious conflicts. Utilizing the principles of implosive therapy (Stampfl & Levis, 1967), Silverman suggested that patients, with the assistance of the analyst, can create and rehearse an emotionally arousing imagery scene that pertains to a critical psychodynamic issue uncovered in the course of the treatment (e.g., primitive wishes related to oral incorporation, incest, or patricide).…”
Section: Level Of Directivenessmentioning
confidence: 99%
“…This raises an important question: Would the direct access and discharge of affect by such techniques by a reversion to Freud’s abreactive method, which he eventually dismissed as unsuccessful? In defense of his use of implosive imagery in psychoanalytic treatment, Silverman (1987) stated that Freud’s early work with the abreactive method assumed the pathogenic importance of warded-off traumatic events, but had not yet fully recognized the role of unconscious wishes in psychopathology. Though Silverman’s technique may be used to implode childhood trauma, its primary goal is uncovering the warded-off affects associated with unconscious wishes and fears.…”
Section: Imagery Techniques: Theoretical and Practical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is Berger's concept of the empathic therapist as the “reader of the patient's novel” who oscillates between the roles of “observer on the scene” and “external observer.” He suggests that we listen to patients describe their lives as if each life were a novel unfolding, always looking for windows to enter their subjective worlds as observers on the scene who empathically share and resonate with their descriptions of their experiences. Though they may resist, we encourage them to tell their stories in terms of vividly described, dramatic action sequences that allow us to join them in that experience—a technique, also described by Silverman (1987), that revives emotional states via visual, auditory, and tactile images. In the role of external observer, we examine the flow of the narrative as a whole, looking for patterns, omissions, errors, and contradictions that reveal deeper unconscious realms of experience, which must be interpreted as hidden elements of the patient's story.…”
mentioning
confidence: 99%